PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP TINGKAT KEPUASAN NASABAH PADA PT. BANK RIAU KEPRI CABANG UTAMA PEKANBARU - Riza Bella Winanda; Lie Othman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The aim of this research is to analyze the implementation of Customer Relationship Management and customer satisfaction level of PT. Bank Riau Kepri Pekanbaru Main Branch and see its effects. Results of the study concluded that the implementation of CRM in PT. Bank Riau Kepri Pekanbaru Main Branch that includes indicators of people, processes and technology have been rated good overall. Customer satisfaction level of PT. Bank Riau Kepri Pekanbaru Main Branch that is seen from the indicator of product quality, service quality, price, and emotional costs are also rated it good. The results of data analysis through SPSS programs, CRM has a strong connection to the customer's satisfaction level. CRM provide variable positive and significant influence on the customer satisfaction rate on variable PT. Bank Riau Kepri Pekanbaru Main Branch, which means that if the variable is improved then the CRM will also cause an increase of the customer satisfaction level.Keyword: customer relationship management, customer satisfaction rate, Bank Riau Kepri